2018
DOI: 10.3892/ol.2018.8444
|View full text |Cite
|
Sign up to set email alerts
|

A real‑world study of treatment patterns and survival outcome in advanced anaplastic lymphoma kinase‑positive non‑small‑cell lung cancer

Abstract: Abstract.Crizotinib is an anti-cancer drug with a substantial beneficial effect in advanced non-small-cell lung cancer (NSCLC) patients harboring anaplastic lymphoma kinase (ALK) rearrangement. However, the real-world data currently available on this drug are limited. Thus, the present study aimed to retrospectively examine the treatment patterns and survival outcome of 83 advanced NSCLC patients with ALK rearrangement in a single center in China. Of the 83 patients enrolled, 33 (39.8%) patients received crizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…e molecular biomarkers may improve the early lung cancer detection [4]. Furthermore, traditional chemotherapy that is based on histopathology is replaced by the individualized precision treatment which is based on carcinogenic factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…e molecular biomarkers may improve the early lung cancer detection [4]. Furthermore, traditional chemotherapy that is based on histopathology is replaced by the individualized precision treatment which is based on carcinogenic factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, our understanding of the molecular characterization of cancer has increased though genomic medicine. The treatment strategy for advanced NSCLC has changed from the traditional chemotherapy based on histopathology to individualized precision treatment based on carcinogenic factors ( Jin et al, 2018 ). Zhu et al indicated that MTA1 might be a momentous biomarker in the diagnosis of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first study to include more than 100 ALK-rearranged NSCLC patients. Regarding prognostic factors, several researchers are conducting studies in ALKrearranged NSCLC patients (7,(25)(26)(27). Among them, there was an interesting report from the research group of Jin et al (7).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding prognostic factors, several researchers are conducting studies in ALKrearranged NSCLC patients (7,(25)(26)(27). Among them, there was an interesting report from the research group of Jin et al (7). According to their report, liver and bone invasions were significant unfavorable prognostic factors in ALKrearranged NSCLC patients (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation